Evaluating the Potential of Three Sperm Surface Antigens as Egg-adhesion Biomarkers for Human Sperm Selection - M Heidari; S Darbandi; M Darbandi; N Amirjanati; M Bozorgmehr; H Zeraati; MM Akhondi; MR Sadeghi (JRI, 2018)
Background: The selection of sperm with good genomic integrity and surface antigens is suggested for improving assisted reproductive technology (ART) outcome. The aim of this study was evaluating the heat shock protein (HSPA2), Dj-1 and serum amyloid P compound (SAP) three sperm surface proteomes as biomarkers for this purpose.  Methods: In this study, semen samples were obtained from 114 men who presented at Avicenna Fertility Clinic for their treatment. The semen characteristics, DNA fragmentation Index (DFI), chromatin maturation index (CMI), biomarker levels, and their embryo quality were considered. The paired-samples t-test and independent-samples t-test were used for analyzing the data and p-values<0.05 were considered significant.  Results: Outcomes exhibited the major reduction in HSPA2, DJ-1 and SAP following reduction in sperm quality and DNA integrity (p<0.001) with cut-off value of 14% (HSPA2), 12% (DJ-1) and 10% (SAP). The specificity of these three biomarkers was 95.2, 73.8 and 88.1%, respectively. Also, DFI (p<0.001), CMI (p<0.05), cleavage (p<0.05), and embryos quality (p<0.001) decreased significantly in abnormal spermiogram (ANS) group in compared with normal spermiogram (¬NS) group. It was shown that DFI was 97.1% in HSPA2, 76.5% in DJ-1 and 94.1% in SAP, and CMI was 95.0%, 75.50% and 87.5%, respectively. The significant correlation was found between of the three biomarkers and CMI (p<0.001), DFI (p<0.001) and embryos quality (p<0.001). Conclusion: By comparing the efficiency of these three biomarkers for selecting sperm with the lowest level of chromatin damages, it seems that selection based on HSPA2 has significance over others.